Does COVID-19 cause erectile dysfunction in males? - Manda, Anusha; Anusha, Are; Balaji, Metikala (International Journal of Basic & Clinical Pharmacology, 2023)
The COVID-19 pandemic brought on by the SARS-COV-2 is a novel healthcare problem. A cytokine storm caused by the hyper-inflammation present in this pandemic leads to serious consequences such micro thrombosis. There have been reports of some male genital organs being impacted by very severe illness instances, leading to erectile dysfunction (ED). Given the high rate of COVID-19 transmission, ED could also be a serious outcome for a sizable portion of the population. It is still little understood and is crucial given that the virus has been discovered in pensile tissue. In this account, we sought to compile potential explanations for the ED development driven by COVID-19. The psychological toll of COVID-19 and endothelial dysfunction, which are among the routes of ED, are now better understood according to recent research.